A The Hubungan Pengetahuan Dengan Perilaku Pemilahan Sampah Medis Dan Non Medis - Trialisfiana, Nadya Putri Eka; Suratmi; Qowi, Nurul Hikmatul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: The behavior of nurses who are less careful in sorting waste will cause work accidents in hospitals because of the results of nursing actions on patients. The characteristics of nurses' behavior in sorting waste can be seen from observation, awareness and intention. Research Objectives: This study aims to determine the relationship between knowledge and the behavior of sorting medical and non-medical waste among nurses at. Methodology: This study used a cross sectional design. The sample in this study was taken using Simple Random Sampling of 54 nurse. This research a questionnaire and observations. Which is analyzed using the Spearman Rank Test. Result: This research shows that there is a positive correlation between the knowledge and behavior in sorting medical and non-medical waste among nurses r = (0.347), p <(0,000). As knowledge increases, nurses' behavior in sorting medical and non-medical waste increases. Conclusions: Based on this research, it is hoped that hospitals can become an illustration and reference in maintaining knowledge, improving management, sorting waste, training and monitoring waste disposal behavior.